Malaria vaccine deployment in Africa: focus on Ghana - Koram, K.A.; Asante, K.P.; Binka, F.N. (Ghana medical journal, 2019)
The announcement by the Ghana Health Service /Ministry of Health at the beginning of May to begin the pilot implementation of the malaria vaccine – RTS,S/AS01 (Mosquirix®) – manufactured by GSK Biologicals was greeted with rumours about conspiracy theories of secret agenda to depopulate Africa through the use of vaccines and all the other stories that are often propagated by the anti vaxxers. This was not unlike the fear and panic spread throughout the country that prevented investigators from conducting clinical trials on new vaccines against the Ebola virus disease a few years ago.
Research Article
Keywords: Malaria; Vaccine; Ghana; Development